Risk of Higher Blood Pressure in 3 to 6 Years Old Singleton Born From OHSS Patients Undergone With Fresh IVF/ICSI - Zhu, Yimin; Fu, Yanling; Tang, Minyue; Yan, Huanmiao; Zhang, Fanghong; Hu, Xiaoling; Feng, Guofang; Sun, Yu; Xing, Lanfeng (Frontiers in Endocrinology, 2022)
Background: Few studies have investigated any association between OHSS and cardiovascular or metabolic function in subsequent children. Objective: To evaluate the effect of ovarian hyperstimulation syndrome (OHSS) on blood pressure of singletons after IVF/ICSI. Study Design: The singlet-center corhort study included 1780 singletons born with IVF/ICSI and 83 spontaneously conceived children from 2003 to 2014. This study analyzed data from follow-up surveys at 3 to 6 years of age. Methods: We recruited 83 children (Group E) spontaneously conceived (SC) as control group and 1780 children born with IVF/ICSI including 126 children born to OHSS-fresh embryo transfer (ET) women (Group A), 1069 children born to non OHSS-ET women (Group B), 98 children conceived by women who developed into moderate or severe OHSS after oocyte retrieval and selected the frozen-thawed embryo transfer (FET) (Group C) , 487 children conceived with non OHSS-FET (Group D). We evaluated cardiometabolic function, assessed BP in mmHg, heart rate, anthropometrics, and metabolic index including glucose, serum lipid, thyroid function, of those children. Main Findings: By the single factor analysis, the SBP and DBP in the SC group (SBP: 99.84±8.9; DBP: 55.27±8.8) were significantly lower than OHSS-ET group's, while the blood pressure was similar between the SC group and other three ART groups. Children had higher BP in the OHSS-ET group (SBP: 101.93±8.17; DBP: 58.75±8.48) than in the non OHSS-ET (SBP: 99.49±8.91; DBP: 56.55±8.02) or OHSS-FET group (SBP: 99.38±8.17; DBP: 55.72±7.94). After using multiple regression analysis to adjust current, early life, parental and ART characteristics, the differences in the SBP and DBP (B (95% confidence interval)) between OHSS-ET and non OHSS-ET remained significant (SBP: 3.193 (0.549 to 2.301); DBP: 3.440 (0.611 to 2.333)). And the BP showed no significant difference complementarily when compared non OHSS-FET group with non OHSS-ET group. In addition, the anthropometrics, fast glucose, serum lipid, and thyroid index did not differ among the ART groups. Principal Conclusions: OHSS might play an independent key role on offspring's BP even cardiovascular function. Electing frozen-thawed embryo transfer for high risk of OHSS population may reduce the risk of the high BP trend.